Mechanical properties of concrete using recycled aggregates obtained from old paving stones (2021)
Nowadays, construction, maintenance, reparation, rehabilitation, retrofitting, and demolition from infrastructure and buildings generate large amounts of urban waste, which usually are inadequately disposed due to high costs and technical limitations. On the other hand, the increasing demand for natural aggregates for concrete production seriously affects mountains and rivers as they are the source of these nonrenewable goods. Consequently, the recycling of aggregates for concrete is gaining attention worldwide as an alternative to reduce the environmental impacts caused by the extraction of nonrenewable goods and disposal of construction and demolition waste (C&DW). Therefore, this article describes the effect on the mechanical properties of new concrete using recycled aggregates obtained from old paving stones. Results show that replacing 50% by weight of the fine and coarse aggregate fractions in concrete with recycled aggregate does not meaningfully affect its mechanical behavior, making the use of recycled aggregates in new precast paving stones possible. Therefore, the latter can reduce environmental impacts and costs for developing infrastructure and building projects.